Between two horizons spanning New Testament studies and systematic theology - Green, Joel B. 1956-; Turner, Max 1947- (Grand Rapids, MI Eerdmans, 2000)
Includes bibliographical references and index.
Keywords: Bible. N.T. -- criticism, interpretation, etc; Doctrine (theology).